Anais Do Workshop De Computação Urbana (CoUrb 2020) 2020
DOI: 10.5753/courb.2020.12361
|View full text |Cite
|
Sign up to set email alerts
|

Towards Federated Learning in Edge Computing for Real-Time Traffic Estimation in Smart Cities

Abstract: The wide proliferation of sensors and devices of Internet of Things(IoT), together with Artificial Intelligence (AI), has created the so-called Smart Environments. From a network perspective, these solutions suffer from high latency and increased data transmission. This paper proposes a Federated Learning (FL) architecture for Real-Time Traffic Estimation, supported by Roadside Units (RSU’s) for model aggregation. The solution envisages that learning will be done on clients with their local data, and fully dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the study by Imteaj and Amini 32 , focused on data collection from smartphones' built-in sensors in smart city infrastructure for transportation, health, and emergency services. Silva et al 33 proposed FL for real-time traffic forecasting using roadside units and suggested exploring different models. Lonare et al 34 presented an aggregated approach to predict vehicle traffic, utilizing decentralized local data securely shared with the server and training with spatial parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study by Imteaj and Amini 32 , focused on data collection from smartphones' built-in sensors in smart city infrastructure for transportation, health, and emergency services. Silva et al 33 proposed FL for real-time traffic forecasting using roadside units and suggested exploring different models. Lonare et al 34 presented an aggregated approach to predict vehicle traffic, utilizing decentralized local data securely shared with the server and training with spatial parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…RELATED WORKS The widespread use of Internet of Things (IoT) sensors and devices, in conjunction with artificial intelligence, has resulted in the creation of "smart environments [13]." However, these solutions have high latency conditions and more information transmission from a network standpoint.…”
Section: IImentioning
confidence: 99%
“…Distinct locations and distinct time in the same location have an effect on the predicted value, this highly dynamic task scenario frequently needs to combine more edge-end information, and for congested vehicles to assign a data set (due to the fact that traffic congestion state and traffic flow are strongly correlated). Furthermore, the location of the camera, speed, and even weather conditions can be included in the input data set for better estimation of traffic behavior [76]. Recently, GNNs have been applied to traffic flow prediction and estimation scenarios, where coordinate information associated with nodes is used to assist in routing to avoid information diffusion [77].…”
Section: B Traffic Status Identificationmentioning
confidence: 99%